2016
DOI: 10.1073/pnas.1602185113
|View full text |Cite
|
Sign up to set email alerts
|

Stress and corticosteroids regulate rat hippocampal mitochondrial DNA gene expression via the glucocorticoid receptor

Abstract: Glucocorticoids (GCs) are involved in stress and circadian regulation, and produce many actions via the GC receptor (GR), which is classically understood to function as a nuclear transcription factor. However, the nuclear genome is not the only genome in eukaryotic cells. The mitochondria also contain a small circular genome, the mitochondrial DNA (mtDNA), that encodes 13 polypeptides. Recent work has established that, in the brain and other systems, the GR is translocated from the cytosol to the mitochondria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 51 publications
2
90
1
4
Order By: Relevance
“…Compared with the Sham group, six genes (ND2, ND3, ND4L, ND5, ND6, and COX3) were upregulated in the I/R group ( p < .05, Figure ), and seven genes (ND1, ND4, COX1, COX2, ATP6, ATP8, and Cytb) were unchanged in the IR group ( p > .05, Figure ). Increasing evidence indicates that inconsistent changes in mitochondrial gene expression decrease the efficiency of ATP production (Cai et al, ; Hao et al, ; Hunter et al, ; Sun, Zong, Gao, Zhu, Tong, & Cao, ), which explains the decrease in the cellular ATP levels observed after I/R injury in this study (Figure c). Consistent with the data shown in Figure , SC1 treatment reversed the changes in mitochondrial gene expression (Figure ) and increased the cellular ATP levels (Figure c).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Compared with the Sham group, six genes (ND2, ND3, ND4L, ND5, ND6, and COX3) were upregulated in the I/R group ( p < .05, Figure ), and seven genes (ND1, ND4, COX1, COX2, ATP6, ATP8, and Cytb) were unchanged in the IR group ( p > .05, Figure ). Increasing evidence indicates that inconsistent changes in mitochondrial gene expression decrease the efficiency of ATP production (Cai et al, ; Hao et al, ; Hunter et al, ; Sun, Zong, Gao, Zhu, Tong, & Cao, ), which explains the decrease in the cellular ATP levels observed after I/R injury in this study (Figure c). Consistent with the data shown in Figure , SC1 treatment reversed the changes in mitochondrial gene expression (Figure ) and increased the cellular ATP levels (Figure c).…”
Section: Resultssupporting
confidence: 55%
“…Mitochondrial DNA encodes genes related to ATP synthesis, such as Complex I (ND1, ND2, ND3, ND4, ND4L, ND5, and ND6), Complex III (CYTB), Complex IV (COX1, COX2, COX3), and ATP synthase genes (ATP6 and ATP8) (Ott, Amunts, & Brown, ). Any persistent alteration of these mitochondrial genes affects the efficiency of ATP production (Cai et al, ; Hao et al, ; Hunter et al, ; Sun, Zong et al, ). Our results showed that the mRNA and 5hmC levels of ND2, ND3, ND4L, ND5, ND6, and COX3 were increased after ischemic injury and that these changes were reversed by the inhibition of Tet2 protein, suggesting that the cellular ATP levels are not solely dependent on the presence of O 2 but also affected by mtDNA 5hmC modification.…”
Section: Discussionmentioning
confidence: 99%
“…By extension, it is believed that molecular changes triggered immediately after stress, transform into persistent waves of gene expression that then accumulate as changes in structural morphology and circuit level dysfunctions. Support for this, comes from work done on signaling cascades mediated by BDNF, endocannabinoids and glucocorticoids (Evanson, Tasker, Hill, Hillard, & Herman, ; Martinowich, Manji, & Lu, ) or the stress‐induced changes in transcription and epigenetic modifications (Hunter et al, ). However, concomitant research on how stress modulates mRNA translation and translation control has lagged behind, being largely assumed to follow the same changes as transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In other cell types, chronic glucocorticoid treatment can reduce the activity of specific mitochondrial electron transport chain complexes and increase mitochondrial ROS production (Tome et al, 2012; He et al, 2017). The underlying mechanisms for these effects are not fully understood, but there are three glucocorticoid response elements (GREs) on the circular mtDNA (Psarra and Sekeris, 2009), where GR likely bind and influence mtDNA gene expression (Psarra and Sekeris, 1813; Hunter et al, 2016). …”
Section: Glucocorticoids Influence Mitochondrial Functionsmentioning
confidence: 99%